Implementasi Aplikasi Mitigasi Bencana Gempa Berbasis Video 360 dengan Efek Visual - Ahmad Faza Al Farisi; Yustifani Putri Candrawulaningsih; Fat'hah Noor Prawita (Universitas Telkom, 2026)
Indonesia faces a high risk of earthquakes due to its location along the Pacific Ring of Fire, where several active tectonic plates converge. Disaster mitigation education has traditionally relied on conventional methods such as brochures, posters, and brief training sessions, which are often less effective in delivering deep understanding. With the advancement of digital technology, especially Virtual Reality (VR), immersive and safe disaster simulations have become more accessible. This study introduces an educational application called SIGAP (Earthquake Simulation in Educational Application), which uses 360-degree video-based VR technology enhanced with realistic visual effects to simulate earthquake conditions. The application allows users to safely experience earthquake scenarios and receive interactive guidance on proper mitigation steps. The development process includes literature review, user needs analysis, interface design, implementation using Unity, and testing for functionality and user comfort. Test results show that SIGAP improves users’ understanding of earthquake safety procedures and offers a more engaging and memorable learning experience. The application also successfully increases user engagement, especially among younger generations who are more familiar with technology. SIGAP is expected to help Indonesian communities become more prepared and responsive in the face of future earthquakes.